A New Class of Distributions Generated by the Extended Bimodal-Normal Distribution. (1st November 2018) - Cortés, Milton A.; Elal-Olivero, David; Olivares-Pacheco, Juan F.
Abstract : In this study, we present a new family of distributions through generalization of the extended bimodal-normal distribution. This family includes several special cases, like the normal, Birnbaum-Saunders, Student'st, and Laplace distribution, that are developed and defined using stochastic representation. The theoretical properties are derived, and easily implemented Monte Carlo simulation schemes are presented. An inferential study is performed for the Laplace distribution. We end with an illustration of two real data sets.